On Determinants of Exchange Market Pressure in Turkey: The Role of Model Uncertainty - Gülden Poyraz; Ahmet İncekara (Journal of Economy Culture and Society)
Macroeconomic and financial indicators have a significant impact on the exchange market pressure (EMP) in Turkey. Despite the huge amount of literature on the subject, there is no study focusing on Turkey that takes into account the role of model uncertainty on exchange market pressure. The role of model uncertainty should be taken into consideration, given the lack of a unique theoretical framework on the exchange markets pressure and a set of numerous explanatory variables. The Bayesian model averaging (BMA) technique is capable of determining as to whether any explanatory variable should be included in the analysis, i.e. the models with high posterior probability. To this end, the determinants of the exchange market pressure index (EMPI) in Turkey for the period of 2010M1-2020M3 are identified using the Bayesian model averaging which takes into account the role of model uncertainty. Model results indicate that the slope of the yield curve, domestic credit growth, the long term yield differentials, and short-term portfolio flows play a significant role as determinants of the exchange rate pressures of Turkey.